Active control of sound through full-sized open windows - Lam, Bhan (2019)
There is a pressing need to address urban sustainability challenges of increasing ambient temperatures and noise levels in densely-populated, high-rise cities. Solutions that utilise active noise control on open windows to reduce indoor noise levels seem promising, as natural ventilation is still maintained. Active noise control utilizes acoustic transducers arranged around the open window to generate a secondary incidence noise that destructively interferes with the real noise. The two most common techniques of transducer arrangement, distributed and boundary layouts, are investigated for the typical single-glazed sliding window. Finite element method is used to establish the control performance of the active noise control system and the passive attenuation provided by the sliding window. Based on the investigated fundamental limits of active control, the distributed layout has consistently yielded better performance than the boundary layout. The distributed-layout method can also reduce noise more effectively than a fully-glazed window. Moreover, sources distributed only in the partial opening of a simulated sliding window can attenuate noise as effectively as the fully-glazed window. The distributed-layout method is tested on a full-sized window, where the active control system has up to 16 channels and evenly distributed across the window opening. In the test with tonal sounds, the feasibility of the active control system is demonstrated. The experimental results have validated the simulation findings for normal incidence plane waves.